Analysis of the Findability of Information on the Website of the Archivo General de la Nación of Colombia - Amaya, Maria Girleza Pérez; de Souza Santos, Mylena; Vechiato, Fernando Luiz; de Albuquerque, Ana Cristina [UNESP] (Universidad de Antioquia, 2023)
Based on the importance that digital information environments currently represent in accessing and retrieving information, we seek to assess the findability of information on the website of the Archivo General de la Nación de Colombia. For this purpose, a checklist was used to analyze the attributes of information findability in informational environments. The mentioned website satisfied some of the attributes, and it is still necessary to implement improvements that suit both these attributes and the current technological requirements. Based on a less technical view, the importance of the participation of Information Science professionals in the design and development process of digital information environments is emphasized.
Análisis de la encontrabilidad de la información en el sitio web del Archivo General de la Nación de Colombia
Análise da encontrabilidade da informação do website do Archivo General de la Nación da Colômbia
Keywords: digital information environments; information architecture; Information findability; website of Archivo General de la Nación of Colombia